Chip morphology: an indicator of response of composite material to grinding. (2nd December 2009) - Anand Ronald, B.; Vijayaraghavan, L.; Krishnamurthy, R.
MMC's can respond differently neither as a ductile material nor as a brittle material. This is reflected in the morphology of the chip collected during grinding of Al/SiCp metal matrix composite. The chip morphology further depends on condition prevailing over the stagnation zone. In this paper, the observation on chip morphology is correlated with the different process parameters like grinding temperature, acoustic emission and vibration. The results show that chip morphology is a reliable indicator of the response of composite material to grinding.